Examine the Relationship between Proinflammatory Cytokines and Breast Cancer - Samia Rashid; Dr Mehak Fatima, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Breast cancer is a complicated illness marked by long-lasting inflammation. Tumor development and progression depend critically on proinflammatory cytokines. Knowing how proinflammatory cytokines interact with breast cancer will shed light on the etiologic factors of the disorder and possible therapeutic targets. Objective: This research sought to investigate how breast cancer related to proinflammatory cytokines. Methods: This quantitative study employed a case-control design. Sample size consisted of 100 healthy controls patients and 100 breast cancer patients aged 25 to 60 years. Using ELISA, serum samples from participants were examined for proinflammatory cytokines (IL-6, TNF-α, IL-1β). Statistical Analysis was performed using SPSS Independent t-test and Pearson correlation. Results: Breast cancer patients had proinflammatory cytokines (IL-6, TNF-“, IL-1²), which was significantly higher than healthy (P <0.001). Cytokine levels and tumor stage were positively correlated (r = 0.456, p <0.001). Conclusion: This research shows a clear link between breast cancer and proinflammatory cytokines. High levels of proinflammatory cytokines could aid in tumor growth and progression. A possible therapeutic approach for breast cancer therapy targeting these cytokines may be found in targeting them.